Factors influencing the behavioral intention of crowd funders to use Crowdfunding-Waqf Model (CWM): Partial least squares approach - Mohd Thas Thaker, Mohamed Asmy; Allah Pitchay, Anwar (Beşiz Publications, 2016)
This study is designed to examine the behavioural intention of donors or crowd funders to use Crowdfunding Waqf Model (CWM). The present study has proposed Crowdfunding Waqf Model to assist Waqf institution in meeting their liquidity constraint in developing Waqf Waqf land in Malaysia. The primary data are collected from the survey administered to donors or crowd funders in the Klang Valley and the analysis is conducted using Partial Least Squares (PLS). Furthermore, the model has validated its acceptance in the field by adopting the Technology Acceptance Model (TAM). This study has revealed that both the perceived usefulness and perceived easy to use are found to have a positive impact on the intention of donors or crowd funders in assisting Waqf institution to develop Waqf land in Malaysia. Furthermore, perceived easy to use has a positive relationship and direct effect with perceived usefulness micro entrepreneurs to use the Crowdfunding Waqf Model.